MENINGKATKAN DAYA SAING UMKM DENGAN INOVASI PADA SABUN YANG RAMAH LINGKUNGAN - Sandari, Tries Ellia; Kartini, Ida Ayu Nuh; Studiviany, Pramita; Djumaifin, Thesalonika; Pranoto, Felix Chandra (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The object of this research is Utopia Soap MSMEs located in Manyar Surabaya. The purpose of its implementation is to conduct training and business assistance in MSMEs, because the potential of the organic soap market is increasingly promising along with increasing public awareness of the importance of products made from natural and environmentally friendly materials. Our organic soap MSMEs still face many challenges, including competition with similar products and lack of access to more modern production knowledge. Utopia Body soap MSMEs are MSMEs formed by several soap artisans in Manyar Surabaya which aims to provide high-quality natural skincare products to the community. Then collaborating with several other soap MSMEs is to increase the competitiveness and profitability of MSMEs through the development of innovative and high-quality organic soap products. This collaboration process involves several stages, ranging from identifying potential collaborations, exchanging knowledge, developing new products, testing and evaluating products, to marketing and selling products. The results of the collaboration created a new organic soap recipe that combines the advantages of each other, so that Utopia MSMEs succeed in improving product quality, product diversification, and business profitability. This service program has also succeeded in improving the sustainability of Utopia's MSME business through product diversification and wider market access.